Innovative Entrepreneurship Learning: Developing an Influential Curriculum for Undergraduate Culinary Students - Luthfi Riyadh Rahman (Universitas Pendidikan Indonesia (UPI), 2023)
In line with the increasing attention to entrepreneurship in the world of catering, this research also developed an innovative entrepreneurship curriculum specifically designed for undergraduate catering students. This research develops and evaluates creative modules consisting of mentoring methods and creative problem solving (CPS) practices for the undergraduate Boga innovative entrepreneurship program at UNY. Mentoring is carried out by practitioner lecturers who come from the industrial field. A quasi-experimental design with a sample of 60 students estimated the causal impact of the educational intervention. Students in the experimental group participated in mentoring and CPS-based culinary business practices for one semester. The results showed that students who received the intervention from practitioner lecturers significantly improved their innovative entrepreneurship as assessed by the T-test. This study examined innovative entrepreneurship through qualitative and quantitative instruments. Findings support the positive impact of education on entrepreneurial potential. In addition, an innovative entrepreneurship development model was developed that can contribute instructional content and learning progressions that can help educators prepare well for practice and predict student progress